Ptosis: Clinical overview, etiology and treatment - Adam Solarz; Szymon Szabelski; Katarzyna Skibicka; Estera Graczyk; Oliwia Cwalina; Joanna Kryślak; Maciej Sokołowski; Karolina Oskroba; Jakub Filip Turcza; Małgorzata Woś (Quality in Sport)
Ptosis is a condition characterized by a low setting of the upper eyelid caused by congenital or acquired dysfunction of the levator muscle. The problem can occur unilaterally or bilaterally, in any age group, and affects over 1 million patients in Poland, with varying degrees of severity. Drooping of the upper eyelid leads to secondary restriction of the visual field, deterioration of vision quality, as well as a subjective decrease in visual acuity. Additionally, it is an aesthetic defect, which consequently negatively impacts the patient's quality of life, self-esteem, and social perception. This article presents key information about ptosis, including clinical implications, etiology, and classification, as well as diagnostic algorithms and methods, and modern surgical treatment approaches.